Oxidative Stress and Microcirculatory Flow Abnormalities in the Ventricles during Atrial Fibrillation - Goette, Andreas; Bukowska, Alicja; Lillig, Christopher; Lendeckel, Uwe (Frontiers in Physiology, 2012)
Patients with atrial fibrillation (AF) often present with typical angina pectoris and mildly elevated levels of cardiac troponin (non ST-segment elevation myocardial infarction; NSTEMI) during an acute episode of AF. However, in a large proportion of these patients significant coronary artery disease is excluded by coronary angiography, which suggests that AF itself influences myocardial blood flow. The present review summarizes the effect of AF on the occurrence of ventricular oxidative stress, redox-sensitive signalling pathways & gene expression, and microcirculatory flow abnormalities in the left ventricle.